The political situation in Yemen During The The Ottoman Rule (923-945IH/1517-1538AD) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research deals with Yemen's political situation in the period between 1517-1538 AD, showing the circumstances it went through after its subordination to the Ottoman Empire, where the Yemeni lands in that period witnessed many wars and conflicts as a result of the multiplicity of conflicting forces over the rule of Yemen, and the control of each of them over a geographically important area within the lands And what made matters worse and more complicated was that these forces not only fought against each other, but each of them witnessed internal conflicts in order to reach the leadership and take over the reins of power, not to mention that none of these forces was able to overthrow the other due to the reliance of each of them on the criteria of its own strength. This was accompanied by the Ottoman Empire’s neglect of what was happening in Yemen and its contentment with its nominal subordination to the Mamluks who were ruling it only, until the Ottomans were forced to effectively establish their influence in Yemen in 1538 AD